Flow Cytometric microsphere-based immunoassay as a novel non-radiometric method for the detection of glutamic acid decarboxylase autoantibodies in type 1 Diabetes Mellitus - Guerra, Luciano Lucas (2014)
The first measurable sign of arising autoimmunity in Type 1 Diabetes Mellitus is the detection of autoantibodies against beta-cell antigens, such as glutamic acid decarboxylase (GAD65). GAD65 autoantibodies (GADA) are usually measured by Radioligand Binding Assay (RBA). The aim of this work was to develop protocols of Flow Cytometric microsphere-based immunoassays (FloCMIA) which involved glutamic acid decarboxylase fused to thioredoxin (TrxGAD65) adsorbed on polystyrene microspheres. Detection of bound GADA was accomplished by the use of anti-human IgG-Alexa Fluor 488 (Protocol A), anti-human IgG-biotin and streptavidindichlorotriazinyl aminofluorescein (DTAF) (Protocol B) or TrxGAD65-biotin and streptavidin- DTAF (Protocol C). Serum samples obtained from 46 patients assayed for routine autoantibodies at Servicios Tecnológicos de Alto Nivel (STAN-CONICET) were analyzed by RBA, ELISA and three alternative FloCMIA designs. Protocol C exhibited the highest specificity (97.8%) and sensitivity (97.4%) and a wide dynamic range (1.00-134.40 SDs). Samples obtained from 40 new-onset diabetic patients were also analyzed to further evaluate the performance of protocol C. The latter protocol showed a sensitivity of 58.6% and a prevalence of 47.5%. Two patients resulted positive only by FloCMIA protocol C and its SDs were higher than RBA and ELISA, showing a significantly wide dynamic range. In conclusion, FloCMIA proved to be highly sensitive and specific, requiring a low sample volume; it is environmentally adequate, innovative and it represents a cost-effective alternative to traditional GADA determination by RBA and/or ELISA; making it applicable to most medium-complexity laboratories.